Influence of knowledge, attitude and skill of good agriculture practice on oil palm production in seedling assistance scheme in Malaysia - Mohd Ishak, Sheilyza (2017)
Oil palm industry has contributed significantly to the Malaysian economy. About 35- 40% of oil palm is being planted by the smallholders which produced about 33% of the total crude palm oil (CPO) on average. Under 9th Malaysian Plan (2006-2010), RM 37.6 million grants in form of good quality of oil palm seedling have been allocated for 5,697 of smallholders through the Oil Palm Seedling Assistance Scheme (SBABB) coordinated by Malaysian Palm Oil Board (MPOB). Results of the previous study showed that only 10% of SBABB participants obtained 10t/ha/year of fresh fruit bunch (FFB) which is the standard or expected output while others produce less than 10t/ha/year which is considered as low yield of output. As 2015-2016, SBABB scheme implemented almost 8-9 years, the productivity should be reviewed either meet the expected yield. The centrality of knowledge, skills and attitude on agriculture has been highlighted by number of researcher as the “fourth factor of production”. However, influence of KAS among SBABB participant on oil palm productivity was unknown and studies on same scenario still lacking in Malaysia. Finding of this study would fill in the research gap and to elucidate the relationship of KAS on GAP on oil palm production among SBABB participants This study was carried out at Sabah and Sarawak whereby a total of 180 respondents have been interviewed using structured questionnaire. The simple random sampling method was used as sampling technique. The questionnaire comprised five (5) sections.The result shows that the most predominant age categories of smallholders are between 48-59 years old and they have medium knowledge and skill in operating their farms. Most of the smallholders owned 1-7ha of the farm. In term of yield, all respondent produce lower than the average production of 20t/ha/year ranging between 10-20t/ha/yr. The result also shows that 65% variation of FFB production caused by seven (7) factors and five (5) of them have a positive relationship to the yield. The 5 factors are farm size, followed by knowledge in farm management, skills operating their farm, perception on MPOB and perception on SBABB itself. These factors are important determinants to enhance the farmers to increase their yield. As the recommendation, smallholders should increase skill and knowledge about farm management via extension services and the application of GAP in their farm.